МАҲАЛЛИЙ СОЛИҚ ТИЗИМИНИНГ УСТУВОР ЙЎНАЛИШЛАРИ ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
In modern society, maintaining a balance between work and personal life has become increasingly challenging. Excessive focus on work can negatively affect health, relationships, and overall well-being. This article explores the importance of work-life balance, its effects on individuals, and strategies to improve it. Practical solutions, including time management, hobbies, social interactions, and technology use, are discussed. A balanced lifestyle enhances productivity, reduces stress, and promotes mental and physical health.